Al-Fi'l Allażī Lam Yusamma Fā‘iluhu fī al-Qur'ān al-Karīm al-Juz' 30 (Taḥlīl Ṣarfī Wa Naḥwī) - M. Aziz Himawan Akbar; Zaim Elmubarok; Moch. Hibatullah Zain (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
The purpose of this study was to determine how passive verbs are formed depending on the kind of verb, tense/aspect, radical letters, originality of form, and amount of consonants. Many verses in Al-Qur'a>n Al-Kari>m juz 30 include the word fi'l majhu>l. This study employs a qualitative research methodology and a library research design. The data used in this study are passive verbs, and the text used for the data is Al-Qur'a>n Al-Kari>m juz 30. A data card is the tool utilized. The documentation approach is used in the data collecting process. Based on previous research and discussion, the researchers concluded that in Al-Qur'a>n Al-Kari>m juz 30, the researchers found 38 passive verbs data with the types: a) passive verbs based on tense/aspect consisting of 29 fi'l ma>d}i data and 9 fi'l mud}ari'; b) passive verbs based on radical letters consist of 22 data fi'l s}ah}i>h{ sa>lim, 4 data fi'l s}ah}i>h} mahmu>z, 3 data fi'l s }a>h}i>h} mud}a'af, 5 data fi'l mu'tal ajwa>f, 3 data fi'l mu'tal na<qis{, and 1 data fi'l mu'tal lafi >f mafru>q; c) passive verbs based on the originality of the form and number of consonants consist of 24 data fi'l s|ula>s|y mujarrad, 3 data fi'l ruba>'y mujarrad, and 11 data s|ula>s|y mazi>d ; d) verbs based on final sound changes consist of 9 mu'rab and 29 mabny.